A second home Missouri's early schools - Thomas, Sue, 1932- (Missouri heritage readers., 2006)
"History of early schools in Missouri, including accounts of teaching materials and methods and schoolday activities. Describes schools in frontier settlements such as Ste. Genevieve. Discusses the beginnings of public education in the 1850s and the contributions of John Berry Meachum, James Milton Turner, and other African American leaders"--Provided by publisher.